PENGARUH VARIASI PARAMETER KECEPATAN TORCH, TEKANAN OKSIGEN DAN JARAK NOZZLE TERHADAP MATERIAL REMOVAL RATE PADA PROSES OTOMASI GAS CUTTING - Robi Subastian; Hari Arbiantara (ROTOR, 2019)
The number of industries that make building, bridge and machine construction are inseparable from the metal cutting process, to produce optimal output, the process is done automatically. Gas Cutting is a metal cutting technique that uses a combination of oxygen gas and fuel. The purpose of this study was to determine the most optimal combination of low carbon cutting fabrication processes with variations in the Torch Speed ​​parameter (mm / min), Oxygen Pressure (Kg / cm2), Nozzle Distance (mm) to produce the greatest MRR using the taguchi method. From the research, the most optimal combination of parameters on MRR is level 3 torch speed of 475 mm / minute, oxygen pressure at level 3 of 7.5 kg / cm2 and nozzle distance at level 2 of 6 mm. with the contribution of torch speed contribution of 87.39%, oxygen pressure of 10.35%, the effect of the nozzle distance parameter of 1.17%.